2020
DOI: 10.1155/2020/5282904
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Vibrations of a Rotor-Active Magnetic Bearing System with 16-Pole Legs and Two Degrees of Freedom

Abstract: The asymptotic perturbation method is used to analyze the nonlinear vibrations and chaotic dynamics of a rotor-active magnetic bearing (AMB) system with 16-pole legs and the time-varying stiffness. Based on the expressions of the electromagnetic force resultants, the influences of some parameters, such as the cross-sectional area Aα of one electromagnet and the number N of windings in each electromagnet coil, on the electromagnetic force resultants are considered for the rotor-AMB system with 16-pole legs. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…(2), we get According to the schematic diagram of the 6-pole Rotor-AMBs given in Fig. 1a, the net electromagnetic forces in and directions after expanding denominators of Eqs (6) using Mclaurin series up to the third-order approximation, can be expressed as follows [1][2][3][4][5][6][7][8][9][10][11][12][13][14]: This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication.…”
Section: A Radial Control Strategy Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…(2), we get According to the schematic diagram of the 6-pole Rotor-AMBs given in Fig. 1a, the net electromagnetic forces in and directions after expanding denominators of Eqs (6) using Mclaurin series up to the third-order approximation, can be expressed as follows [1][2][3][4][5][6][7][8][9][10][11][12][13][14]: This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication.…”
Section: A Radial Control Strategy Mathematical Modelmentioning
confidence: 99%
“…Therefore, AMBs is an inherently nonlinear system, where every design for AMBs has its own dynamical behaviors. Therefore, many research articles have been dedicated to explore the nonlinear dynamics for different configurations of Rotor-AMBs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Ji et al [1] explored the nonlinear dynamical behaviors of the four-pole Rotor-AMBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamical characteristics and motion bifurcation of the sixteen-pole AMBS system were explored under different control algorithms [17][18][19][20][21][22][23]. Saeed et al [17,18] introduced a detailed investigation for the sixteen-pole system with constant stiffness coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the rotor system has quartic stable periodic motions in the case of Cartesian control, while the system behaves like a Duffing oscillator with a hardening spring characteristic at the radial control case. Zhang and his team introduced a detailed investigation for the sixteen-pole AMBS' having time-varying stiffness coefficients [19][20][21][22][23]. The capability of the active magnetic bearings system on generating a controllable magnetic attractive force without physical contact with the rotor has attracted scientists and engineers to employ the AMBS with some control algorithms to serve as an adaptive actuator that can be Appl.…”
Section: Introductionmentioning
confidence: 99%